2002
DOI: 10.1046/j.1365-2044.2002.02785.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, controlled trial of cognitive and psychomotor recovery from midazolam sedation following reversal with oral flumazenil

Abstract: Flumazenil is traditionally administered intravenously to reverse the adverse effects of over sedation with benzodiazepines. The aim of this study was to test postoperative cognitive and psychomotor recovery from midazolam conscious sedation, following reversal with orally administered flumazenil. It was hypothesised that when administered by the oral route, flumazenil may enhance recovery over a prolonged period, thus increasing safety. Eighteen patients requiring intravenous midazolam sedation for dental tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Cognitive testing was initiated 5 min postdosing and identified significant decline on tests of simple and choice reaction time, immediate and delayed recall, as well as word and picture recognition tasks when compared to a no-drug control condition. Other recent studies have observed similar results (Girdler et al, 2002;Rogers et al, 2002). The timecourse of oral midazolam is well-established, with time to maximum plasma concentration (C max ) occurring within 1 hr post-dosing, and a good correlation observed between plasma levels and clinical effects (Kanto, 1985).…”
Section: Introductionmentioning
confidence: 66%
“…Cognitive testing was initiated 5 min postdosing and identified significant decline on tests of simple and choice reaction time, immediate and delayed recall, as well as word and picture recognition tasks when compared to a no-drug control condition. Other recent studies have observed similar results (Girdler et al, 2002;Rogers et al, 2002). The timecourse of oral midazolam is well-established, with time to maximum plasma concentration (C max ) occurring within 1 hr post-dosing, and a good correlation observed between plasma levels and clinical effects (Kanto, 1985).…”
Section: Introductionmentioning
confidence: 66%
“…Midazolam seems to be a suitable pharmacological agent for the treatment of agitation in this population, considering that the preferred drugs are those with short-term effectiveness that contribute to tranquilization but do not delay recovery; all the more so as an effective antidote exists. 45 The two main adverse reactions reported in our review appear to be more common in the populations of patients with mean age over 60 years but also in the situations where Midazolam was used in combination with other drugs. However, rates of these adverse effects remain lower than those described with neuroleptic drugs whose adverse effects rates are age-dependent and not dose-dependent.…”
Section: Re Sults and Discussionmentioning
confidence: 70%
“…Midazolam seems to be a suitable pharmacological agent for the treatment of agitation in this population, considering that the preferred drugs are those with short‐term effectiveness that contribute to tranquilization but do not delay recovery; all the more so as an effective antidote exists …”
Section: Resultsmentioning
confidence: 99%
“…Flumazenil is currently available only for intravenous (IV) injection and in a low concentration formulation, a fact that limits its use for some important indications [9]. However, it was found to be effective when used by other routes of administration such as oral [10][11][12] , intranasal [13,14] , intraoral injection [15] , endotracheal [16] , and sublingual [17] . The onset of flumazenil action following IV injection is rapid and effective as shown for the treatment of HE [6,7].…”
Section: Discussionmentioning
confidence: 99%